PENGARUH PENGGUNAAN APLIKASI CISCO IT ESSENTIALS VIRTUAL DESKTOP TERHADAP HASIL BELAJAR SISWA KELAS X SMA PADA SUBMATERI PERANGKAT KERAS KOMPUTER - Anggi Dwi Wiyani Putri; Reni Kurnia; Alkadri Masnur; Rosmaria Rosmaria (Jurnal Manajemen Pendidikan, 2026)
This study aimed to examine the effect of the Cisco IT Essentials Virtual Desktop application on the learning outcomes of tenth-grade students in the Computer Hardware subtopic at SMAN 1 Matur. A quantitative approach with a quasi-experimental method and Pretest–Posttest Control Group Design was employed. The sample consisted of 62 students selected through purposive sampling, comprising 31 students in the experimental class and 31 students in the control class. Data were collected using a validated and reliable 25-item multiple-choice test and analyzed through normality, homogeneity, and t-tests. The results showed that the experimental class achieved a higher mean score (83.74) than the control class (71.16). Hypothesis testing revealed that the calculated t-value was greater than the critical t value (5.4046 > 2.000) at a significance level of 0.05, indicating a significant positive effect of the application on students’ learning outcomes. The novelty of this study lies in the use of Cisco IT Essentials Virtual Desktop as a virtual simulation-based learning medium in senior high school Informatics education to support practical learning despite limited laboratory facilities.